Effects of hydrogen addition to the intake air on performance and emissions of common rail diesel engine - YILMAZ, İLKER TURGUT (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
This paper reports an investigation of the engine performance and emissions of an engine burning hydrogen-enriched diesel fuel. Hydrogen was chosen as the secondary fuel for its renewability in the long term and overall sustainability as a fuel. A four-cylinder, four-stroke, 1.461-L diesel engine with a common rail injection system was used for our tests. The cylinder pressures, rate of heat releases (ROHRs), brake specific energy consumptions (BSECs), brake thermal efficiencies (BiEs), exhaust gas temperatures (EGTs), and exhaust emissions were investigated under 50 Nm, 75 Nm and 100 Nm engine loads at 1750 rpm. Diesel fuel was injected directly to combustion chamber while hydrogen was continuously inducted into the intake manifold at two different flow rates while the original settings of the engine's electronic control unit were preserved. Results showed that hydrogen enrichment decreased HC and CO2 emissions and ROHRs, and increased EGTs and cylinder pressures under all conditions we tested. NOx emissions decreased with a 20 lpm flow rate and increased with a 40 lpm flow rate. Hydrogen also had a positive effect on BSEC and BTE, especially with low engine loads. Overall, hydrogen enrichment increases efficiency and reduces carbon-based emissions, all without major engine modifications. (C) 2017 Published by Elsevier Ltd.
Keywords: Hydrogen addition; Dual-fuel diesel engine; Heat release; Performance; Exhaust emissions; DUAL-FUEL MODE; COMPRESSION IGNITION ENGINE; COMBUSTION CHARACTERISTICS; EXHAUST EMISSIONS; SECONDARY FUELS; PRODUCER GAS; ENERGY-SHARE; CI ENGINE; INJECTION; CYLINDER